2024
DOI: 10.31616/asj.2023.0409
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Concept and Technical Considerations of Biportal Endoscopic Spine Surgery for Lumbar Spinal Stenosis

Jon Park,
Dong-Ki Ahn,
Dae-Jung Choi

Abstract: Decompression is a major component of surgical procedures for degenerative lumbar spinal stenosis (LSS). In addition to sufficient decompression to guarantee the relief of neurological pain, compensating surgical instability after wider laminectomy and foraminotomy and instrumentation with caging and fusion with grafting are performed to secure or restore the foraminal dimension and correct coronal/sagittal imbalance for longer survival of the adjacent segment. Endoscopic spinal surgery (ESS) has been develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Lower back pain ranks among the foremost causes of disability worldwide, and its predominant etiology is lumbar degenerative spinal disease [1,2], which encompasses various pathological changes in the lumbar spine, including disc degeneration, facet joint arthritis, segmental slip, and spinal stenosis. Lumbar degenerative spinal diseases such as lumbar spondylolisthesis and spinal stenosis significantly affect the quality of life of several patients [3][4][5][6][7]. As the global elderly population continues to grow, there is an increasing number of individuals affected by lumbar degenerative spinal diseases, leading to an increased demand for treatment aimed at enhancing their quality of life [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Lower back pain ranks among the foremost causes of disability worldwide, and its predominant etiology is lumbar degenerative spinal disease [1,2], which encompasses various pathological changes in the lumbar spine, including disc degeneration, facet joint arthritis, segmental slip, and spinal stenosis. Lumbar degenerative spinal diseases such as lumbar spondylolisthesis and spinal stenosis significantly affect the quality of life of several patients [3][4][5][6][7]. As the global elderly population continues to grow, there is an increasing number of individuals affected by lumbar degenerative spinal diseases, leading to an increased demand for treatment aimed at enhancing their quality of life [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It offers a clear view of the surgical eld under water medium, exible operation under dual channels, an adaptable and variable surgical approach, and the use of more surgical instruments [8,9]. Jon Park et al reported the "four-level stenosis protocol" to evaluate the foraminal and lateral recess zones [10]. A contralateral sublaminar approach was recommended for the dominant foramen-to-extraforaminal stenotic pathology or disk extrusion at level 1 or 2 combined with lateral recess stenosis [11].…”
Section: Introductionmentioning
confidence: 99%